Covid 19: Public Knowledge and Preventive Behaviors - Wantiyah Wantiyah; Fahmi Essa Syafriansyah; Rismawan Adi Yunanto (The Indonesian Journal of Health Science, 2021)
Background and Aim: Coronavirus disease 2019 (COVID-19), an infectious disease caused by severe acute respiratory syndrome coronavirus is being the world serious problem with the total case that has elevating dramatically. The people knowledge about Covid-19 is prominent aspect in deal with the behavior to prevent the transmission of covid-19. The aim of this research is to identify the relationship between the level of knowledge and covid-19 prevention behavior within population.Methods: This research used cross sectional approach. The survey was conducted using questionnaires that was requested and then collected online used Google Forms among 289 respondents on March-April 2021. The questionnaires examined the demographic of respondents’, covid-19 knowledge and preventive behaviors.  This research was conducted in a district at Lumajang, East Java, Indonesia.Results: The Majority (79,6 %) of respondents were at good level of knowledge about Covid-19, 18,3 % have enough knowledge, and the rest  (2,1 %) were at poor level. Meanwhile, for the preventive behavior, Most respondents (84,8%) have implemented good behaviors in preventing the transmission such as doing hand washing, wearing mask, and maintaining physical or social distancing.Conclusion: There is a correlation between the level of knowledge about covid-19 and preventive behaviors (p: 0,001; r: 0,568; α: 0,005). Hence, the higher the knowledge, the better the behavior to prevent the transmission of Covid-19. Therefore, public awareness to access the right information about covid-19 is essential to enhance people in performing preventive behaviors during pandemic era.